æ—¥æœ¬èªžãƒ´ã‚©ã‚¤ã‚¹æ§‹æ–‡ã®æŒ‡æ¨™çš„æ©Ÿèƒ½ã¨è©±è€…ã®é¸æŠž - Otsuka, Hiroko (Universitas Pendidikan Indonesia (Indonesia University of Education), 2019)
In previous researches Japanese voice constructions were examined as devices for managing discourse coherence by indicating a person as the focus of attention or of spearker’s empathy. However, in that discourse function a speaker cannot choose the function because it is automatically determined by grammatical and cognitive ways. Previous studies rarely studied the context constitutive choice made by a speaker in every actual language use. This paper aims to explain the functions of Japanese voice constructions which can potentially be a set of options for a speaker’s choice in a discourse, and then examines the speaker’s motivation for the choice made. Introspective and intuitive research method is used to explain the set of options and motivations of speaker’s choice, and each set is assumed to be formed paradigmatically based on functional linguistic theory. The functions of constructions are explained as indexical functions which is developed in the theory of anthropological linguistics. Indexical functions examined here are conventional grammatical knowledges shared in a particular language community. The data used are personal narrative ones. Therefore, the speaker’s focus of attention or empathy no longer need to be questioned here, because in the personal narratives the speaker itself is cognitively the focus of attention. The analysis shows that the indexical functions of constructions chosen by the speaker is roughly divided into two types of indexicals, the first is referential indexicals which express the locus of speaker, directionality, causality, and affectedness of actions, evaluative attitudes towards events, social statuses and powers, and mental attitudes. The second is nonreferential indexicals that express socio-cultural attitudes.